Epithelial N-cadherin and nuclear β-catenin are up-regulated during early development of human lung - Kaarteenaho, Riitta (BioMed Central, 2010)
BACKGROUND: The aim of this study was to analyze the cell-specific expression of E- and N-cadherin and β-catenin in developing human lung tissues from 12 to 40 weeks of gestation. METHODS: Fortyseven cases of developing human lung including pseudoglandular, canalicular, saccular and alveolar periods were analyzed by immunohistochemisty for E- and N-cadherin and β-catenin and twentyone cases were also investigated by RT-PCR for E- and N-cadherin and β-catenin. For identifying the lung cells, the sections were also stained with antibodies against thyroid transcription factor-1 (TTF-1) and caveolin-1. Normal adult lung tissue was used as a control. E-cadherin was strongly expressed in epithelium of bronchi and large bronchioles from week 12 onwards and it was also positive in alveoli in pretype II cells and type II cells. N-cadherin was present in most of the epithelial cells of bronchi and the largest bronchioles during the pseudo-glandular and canalicular periods. N-cadherin was not detected in epithelium of developing alveoli. β-catenin was strongly membrane-bound and positively expressed in bronchial epithelium from week 12 to week 40; it showed nuclear positivity in both developing airway epithelium and in the cells underneath the epithelium during pseudo-glandular period and to a lesser degree also in the canalicular period. β-catenin was positive in pretype II cells as well as in type I and type II pneumocytes within alveoli. RT-PCR analyses revealed detectable amounts of RNAs of E- and N-cadherin and β-catenin in all cases studied. The amounts of RNAs were higher in early stages of gestation. CONCLUSIONS: E-cadherin is widely expressed in bronchial and alveolar epithelial cells. N-cadherin exhibit extensive epithelial positivity in bronchial epithelial cells during early lung development. The presence of β-catenin was observed in several cell types with a distinct location in tissue and cells in various gestational stages, indicating that it possesses several roles during lung development. The expressions of protein and mRNAs of E- and N-cadherin and β-catenin were higher in early gestation compared to of the end. Moreover, the expressions of these factors were higher during the lung development than in the adult human lung.